Observation on Establishment of Tectona GrandisLinn. and Gmelina Arborea Roxb. - Bisaria, A. K.; Tyagi, Shiv Ram; Ahanger, Mohammad Abass (Indian Forester, 2014)
Eighteen month old plants of Tectona grandis and Gmelina arborea were established at Tapovan, Gwalior (MP). The growth parameters studied were plant height, width, flowering percentage, per cent reduction in number of plants and plants successfully established. Saplings of Tectona grandis showed better adaptation as compared to Gmelina arborea. Though per cent establishment of Gmelina arborea was less but their height was greater as compared to Tectona grandis.